Supernumerary mesiodentes with familial character: A clinical report - Almeida, Janete Dias [UNESP]; Guimarães Cabral, Luiz Antonio [UNESP]; Martins Gomes, Ana Paula [UNESP]; Moraes, Elisabete [UNESP] (My University, 1995)
This article reports the oeurrence of mesiodentes in three siblings. The etiology of this condition is discussed and genetic considerations, such as modes of inheritance and prevalence, are discussed. © Quintessence Publishing Co. Inc. All rights reserved.